LAMR1 restricts Zika virus infection by attenuating the envelope protein ubiquitination. Issue 1 (1st January 2021) - Hu, Dingwen; Wang, Yingchong; Li, Aixin; Li, Qin; Wu, Caifeng; Shereen, Muhammad Adnan; Huang, Shanyu; Wu, Kailang; Zhu, Ying; Wang, Wenbiao; Wu, Jianguo
ABSTRACT: Zika virus (ZIKV) infection can cause severe neurological disorders, including Guillain–Barre syndrome and meningoencephalitis in adults and microcephaly in fetuses. Here, we reveal that laminin receptor 1 (LAMR1) is a novel host resistance factor against ZIKV infection. Mechanistically, we found that LAMR1 binds to ZIKV envelope (E) protein via its intracellular region and attenuates E protein ubiquitination through recruiting the deubiquitinase eukaryotic translation initiation factor 3 subunit 5 (EIF3S5). We further found that the conserved G282 residue of E protein is essential for its interaction with LAMR1. Moreover, a G282A substitution abolished the binding of E protein to LAMR1 and inhibited LAMR1-mediated E protein deubiquitination. Together, our results indicated that LAMR1 represses ZIKV infection through binding to E protein and attenuating its ubiquitination.